Traumatic brain injury in patients with facial fracture : A challenge for the clinician? - Kokko, Linda; Puolakkainen, Tero; Thorén, Hanna; Piippo-Karjalainen, Anna; Suominen, Auli; Snäll, Johanna (France, 2025)
Objective
This study aimed to evaluate the occurrence and clinical predictors for missed traumatic brain injury (TBI) diagnosis at primary evaluation in facial fracture patients. The specific aim was to compare the risk between adults and elderly patients.
Materials and methods
A retrospective study was performed, and data were collected from medical records. All adult facial fracture patients with associated TBI and a primary Glasgow Coma Scale score of 13 or more diagnosed and treated between 2013 and 2018 were included. The elderly group comprised patients aged at least 65 years at the time of injury.
Results
Altogether 253 patients with facial fracture and associated TBI were assessed. In 7.1 % of the cases, the diagnosis of TBI was missed in primary evaluation and thus delayed. When the different age groups were compared, the elderly had a 2.8-fold risk of missed TBI diagnosis (95 % CI 1.1–7.2, p=.0349).
Conclusions
Facial fracture patients are at significant risk of the diagnosis of associated TBI being missed at primary evaluation. Especially elderly patients with other than high-energy trauma mechanism, such as falling on ground level, are at risk of missed TBI diagnosis. Thus, patients with facial fracture should be carefully evaluated to exclude potential TBI. Assessment should occur in trauma centres where multiprofessional evaluation of these patients is routine.